A Mathematical Model for Accessing Dengue Hemorrhagic Fever in Infants - Camargo, F. A.; Oliveira, T. M.; Rodrigues, D. S.; Mancera, P. F. A.; Santos, F. L. P. (Trends in Computational and Applied Mathematics, 2022)
A mathematical model was developed to describe the dynamics of the primary infection of dengue virus in infant who were born of a mother immune to some serotype of the dengue virus. The model is given by a system of nonlinear ordinary differential equations with the time-dependent variables for the number of DENV antibodies of the infant transferred from their immune, uninfected and infected monocytes and dengue virus. The mathematical analysis was carried out where the conditions for the existence of the disease-free equilibrium and the endemic equilibrium were established. The numerical simulations were performed considering different scenarios for R0 (Basic Reproductive Number), illustrating the global convergence of the numerical results for the equilibrium points. The results are in agreement with our derived global stability analysis. It can be concluded that the DHF in the infants could occur in the peaks observed for the infected monocytes and dengue virus.